2020
DOI: 10.3389/fpubh.2020.00474
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis as an Initial Presentation of COVID-19: A Case Report

Abstract: The common presenting symptoms of fever, fatigue, and mild respiratory symptoms like dry cough, are associated with COVID-19, however, patients can also develop neurological manifestations like headache, anosmia, hyposmia, dysgeusia, meningitis, encephalitis, and acute cerebrovascular accidents during the disease. Although very rare, these neurological manifestations are sometimes the sole initial presenting complaint of COVID-19. This case report discusses patients where the initial presenting symptoms seemed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 13 publications
0
23
0
1
Order By: Relevance
“…Although the CSF RBC count was only reported for 61/430 (14%) patients [ 22 , 28 , 29 , 31 , 35 , 39 , 40 , 44 , 73 , 74 , 77 , 78 , 81 , 89 , 92 , 102 , 110 , 118 , [120] , [121] , [122] , [123] , 128 , 133 , 134 , [138] , [139] , [140] , 156 , 165 , 166 , [172] , [173] , [174] , [175] , [176] , 180 , 184 , 188 , 191 , 192 , 198 , 202 , 204 , 208 , 215 , 220 , 225 , 227 , 233 , 241 , 242 , 246 ], the CSF white blood cell (WBC) count was provided for 409/430 (95%) patients, 270 (66%) of whom had >0 cells/μL, >1 WBC:1,000 RBC or were noted to have “pleocytosis” ( Fig. 3 ) [ [5] , [6] , [7] , [8] , 10 , 13 , [15] , [16] , [17] , [18] ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the CSF RBC count was only reported for 61/430 (14%) patients [ 22 , 28 , 29 , 31 , 35 , 39 , 40 , 44 , 73 , 74 , 77 , 78 , 81 , 89 , 92 , 102 , 110 , 118 , [120] , [121] , [122] , [123] , 128 , 133 , 134 , [138] , [139] , [140] , 156 , 165 , 166 , [172] , [173] , [174] , [175] , [176] , 180 , 184 , 188 , 191 , 192 , 198 , 202 , 204 , 208 , 215 , 220 , 225 , 227 , 233 , 241 , 242 , 246 ], the CSF white blood cell (WBC) count was provided for 409/430 (95%) patients, 270 (66%) of whom had >0 cells/μL, >1 WBC:1,000 RBC or were noted to have “pleocytosis” ( Fig. 3 ) [ [5] , [6] , [7] , [8] , 10 , 13 , [15] , [16] , [17] , [18] ...…”
Section: Resultsmentioning
confidence: 99%
“…CSF pleocytosis may be indicative of infection, inflammation or other CNS injury [ 247 ]. There were 29/409 patients (7%) who had a CSF WBC count of 21–100 cells/μL, all of whom had symptoms that localized to the CNS; 10 (34%) of these patients had CSF RBC counts provided, all of whom had a CSF RBC count of <300 cells/μL; Naz et al described a patient with headache and indicated that CSF was consistent with viral meningitis, but the CSF WBC count was unclear, as it was noted that he had 90 lymphocytes and 10 neutrophils (no units provided so we were unsure if these were percentages or numbers of cells), so we classified these findings as “increased WBC.” [ 10 , [27] , [28] , [29] , 44 , 75 , 79 , [127] , [128] , [129] , 140 , 145 , 154 , 160 , 161 , 170 , 173 , 183 , 184 , 187 , 198 , 205 , 208 , 216 ]
Fig. 3 Cerebrospinal fluid white blood cell count results.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of smell and taste are the most common peripheral nervous system symptoms which were consistently presented early during infection, emerging from 0 to 3 days of confirmation (Naz et al, 2020). Most patients recover after 1 to 3 weeks, as reported by a study done in an Egyptian hospital (n=65), where more than 80% patients experienced partial or complete loss of smell and taste (Al-Zaidi & Badr, 2020).…”
Section: Loss Of Smell and Tastementioning
confidence: 83%
“…Обращают на себя внимание случаи развития нейроковида, в том числе тяжелых форм (менингит, энцефалит, миелит), без предшествующих типичных респираторных проявлений [161][162][163]. Это порождает вопросы о том, что же в этих случаях служит входными воротами для инфекции, каким образом возбудитель может преодолевать гематоэнцефалический барьер при гематогенной диссеминации первично респираторной инфекции?…”
Section: актуальная проблемаunclassified